A domestic cat whole exome sequencing resource for trait discovery - Alana R. Rodney (Nature Portfolio, 2021)
Abstract Over 94 million domestic cats are susceptible to cancers and other common and rare diseases. Whole exome sequencing (WES) is a proven strategy to study these disease-causing variants. Presented is a 35.7 Mb exome capture design based on the annotated Felis_catus_9.0 genome assembly, covering 201,683 regions of the cat genome. Whole exome sequencing was conducted on 41 cats with known and unknown genetic diseases and traits, of which ten cats had matching whole genome sequence (WGS) data available, used to validate WES performance. At 80 × mean exome depth of coverage, 96.4% of on-target base coverage had a sequencing depth > 20-fold, while over 98% of single nucleotide variants (SNVs) identified by WGS were also identified by WES. Platform-specific SNVs were restricted to sex chromosomes and a small number of olfactory receptor genes. Within the 41 cats, we identified 31 previously known causal variants and discovered new gene candidate variants, including novel missense variance for polycystic kidney disease and atrichia in the Peterbald cat. These results show the utility of WES to identify novel gene candidate alleles for diseases and traits for the first time in a feline model.